Atorvastatin induces MicroRNA-145 expression in HEPG2 cells via regulation of the PI3K/AKT signalling pathway. (1st May 2018) - Docrat, Taskeen Fathima; Nagiah, Savania; Krishnan, Anand; Naidoo, Dhaneshree B.; Chuturgoon, Anil A.
Abstract: The use of statins as a potential cancer drug has been investigated; however the molecular mechanisms involved in their anti-oxidant, anti-proliferative and anti-cancer effects remain elusive. In our study, we investigated the involvement of downstream mevalonate products that mediate the anti-oxidant and anti-proliferative effects of Atorvastatin (Ato), and its effect on microRNA-145 expression in HepG2 hepatocellular carcinoma cells. An amorphous soluble form of Ato was prepared and found to be cytotoxic in vitro [IC50 (1.2 mM); 48 h]. Atorvastatin induced a dose-dependent increase in cell mortality with a concomitant depletion of intracellular ATP levels ( p = 0.005); significantly increased extracellular nitrite levels ( p = 0.001) and decreased lipid peroxidation ( p = 0.0097) despite a decrease in GSH. The intrinsic apoptotic pathway was activated via increased caspase −9 ( p < 0.0001) and −3/7 ( p = 0.0003) activities. Increased protein expression of pGSK3-(α/β) ( p = 0.0338), p53 ( p = 0.0032), Mdm2 (p < 0.0001), with significantly diminished levels of PI3K (p = 0.0013), pAKT ( p = 0.0035), and Akt ( p = 0.0077), indicated that Ato-mediated cell death occurred via inhibition of the PI3K/Akt pathway. Additionally, the expression of PI3K ( p = 0.0001) and c-myc ( p = 0.0127) were also downregulated, whilst and miRNA-145 ( p = 0.0156) was upregulated. In conclusion our data strongly indicates a plausible mechanism involved in the cytotoxic effects of Ato and is the first study to show that Ato modulates miR-145 expression in hepatocytes. ≤ Highlights: Atorvastatin (Ato) increased liver cell mortality and decreased [ATP]. Ato increased activites of caspases- 9, 3 and 7. Ato increased protein expression of pGSK3, p53 and Mdm2. Ato decreased protein expression of PI3K, pAKT and AKT. Ato modulates expression of miR-145.